2020
DOI: 10.1002/bkcs.11971
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Cytosine and Uracil from Cyanoacetylaldehyde and Guanidine: A Computational Study

Abstract: Potential energy surface for the formation of cytosine and uracil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…5 For example, Kaur and Sharma 6 have performed computational simulations, using density-functional theory (DFT), of the possible free radical ammonia-mediated pathways for cytosine and uracil formation, where cyanoacetaldehyde plays a key role, and, more recently, a computational study of water- catalyzed synthetic route to pyrimidine bases starting from cyanoacetaldehyde and guanidine has been presented. 7 Due to its relevance in the above discussed reactions, cyanoacetaldehyde (and its enolic isomers) has been the subject of computational and experimental IR 8 and microwave 9 spectroscopic characterization in order to facilitate its search in the ISM by comparison of laboratory spectra with those recorded by modern and powerful telescopes. These studies also showed that cyanoacetaldehyde conformers are more stable than the enolic isomers due to the presence of a nitrile group which weakly interacts with the hydrogen atom of the carbonyl group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 For example, Kaur and Sharma 6 have performed computational simulations, using density-functional theory (DFT), of the possible free radical ammonia-mediated pathways for cytosine and uracil formation, where cyanoacetaldehyde plays a key role, and, more recently, a computational study of water- catalyzed synthetic route to pyrimidine bases starting from cyanoacetaldehyde and guanidine has been presented. 7 Due to its relevance in the above discussed reactions, cyanoacetaldehyde (and its enolic isomers) has been the subject of computational and experimental IR 8 and microwave 9 spectroscopic characterization in order to facilitate its search in the ISM by comparison of laboratory spectra with those recorded by modern and powerful telescopes. These studies also showed that cyanoacetaldehyde conformers are more stable than the enolic isomers due to the presence of a nitrile group which weakly interacts with the hydrogen atom of the carbonyl group.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, theoretical investigations have been undertaken to study the possible pyrimidine and purine synthetic routes . For example, Kaur and Sharma have performed computational simulations, using density-functional theory (DFT), of the possible free radical ammonia-mediated pathways for cytosine and uracil formation, where cyanoacetaldehyde plays a key role, and, more recently, a computational study of water-catalyzed synthetic route to pyrimidine bases starting from cyanoacetaldehyde and guanidine has been presented …”
Section: Introductionmentioning
confidence: 99%